2020
DOI: 10.2147/bctt.s269519
|View full text |Cite
|
Sign up to set email alerts
|

<p>Mirna21 Expression in the Breast Cancer Tumor Tissue is Independent of Neoadjuvant Chemotherapy</p>

Abstract: Introduction: MicroRNA-21 (miRNA-21) has been described as one of the most significantly upregulated miRNAs in human breast cancer. However, limited knowledge exists on miRNA-21 expression in breast cancer tissue after neoadjuvant chemotherapy (NAC). Purpose: The aim of this study was to assess miRNA-21 expression in the tumor tissues of Brazilian patients with breast cancer who underwent NAC and its correlation with clinicopathological variables. Patients and Methods: Utilizing qRT-PCR, miRNA-21 expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Circulating MiRNAs are emerging as new diagnostic and prognostic biomarkers for BC; there help predict tumor response to specific chemotherapeutic drugs 8 . MicroRNA-21 has been described as one of the most significantly up-regulated miRNAs in human breast cancer regardless of pre-vious exposure to chemotherapy treatment which reinforces its role as an "oncomiR" and a potential biomarker 9 . The study aims to analyze the expression quantity of serum (miR-21-5p) and compare it with one of the most widely used serum markers (CA15-3), then check sensitivity, specificity, accuracy, quality and discrimination power comparison for both miRNA-21 and CA15-3 markers.…”
Section: Introductionmentioning
confidence: 82%
“…Circulating MiRNAs are emerging as new diagnostic and prognostic biomarkers for BC; there help predict tumor response to specific chemotherapeutic drugs 8 . MicroRNA-21 has been described as one of the most significantly up-regulated miRNAs in human breast cancer regardless of pre-vious exposure to chemotherapy treatment which reinforces its role as an "oncomiR" and a potential biomarker 9 . The study aims to analyze the expression quantity of serum (miR-21-5p) and compare it with one of the most widely used serum markers (CA15-3), then check sensitivity, specificity, accuracy, quality and discrimination power comparison for both miRNA-21 and CA15-3 markers.…”
Section: Introductionmentioning
confidence: 82%
“…Related to multiple cancers [ 50 , 51 ], miR-21 targets and inhibits the tumor-related genes of programmed cell death 4 (PDCD4), and phosphatase and tensin homolog (PTEN) [ 52 ]; it is involved in tumor angiogenesis, which is closely related to tumor cell proliferation, invasion, and drug resistance [ 53 , 54 ]. We found that miR-21 was upregulated in the four synchronous desmoids showing significant nuclear positivity for β-catenin, in line with experimental evidence that overexpressed miR-21-5p associated with mutated CTNNB1 promoted increased phosphorylation of β-catenin and nuclear translocation in colorectal cancer cell lines [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…ΔΔCT values were derived from treated samples compared to control samples, determining fold changes using the formula 2^(-ΔΔCT). This technique enabled rapid and precise evaluation of gene expression alterations in response to experimental conditions[ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%